Molecular archaeoparasitology identifies cultural changes in the Medieval Hanseatic trading centre of Lübeck. Issue 1888 (10th October 2018) - Flammer, Patrik G.; Dellicour, Simon; Preston, Stephen G.; Rieger, Dirk; Warren, Sylvia; Tan, Cedric K. W.; Nicholson, Rebecca; Přichystalová, Renáta; Bleicher, Niels; Wahl, Joachim; Faria, Nuno R.; Pybus, Oliver G.; et al.
Abstract : Throughout history, humans have been afflicted by parasitic worms, and eggs are readily detected in archaeological deposits. This study integrated parasitological and ancient DNA methods with a large sample set dating between Neolithic and Early Modern periods to explore the utility of molecular archaeoparasitology as a new approach to study the past. Molecular analyses provided unequivocal species-level parasite identification and revealed location-specific epidemiological signatures. Faecal–oral transmitted nematodes ( Ascaris lumbricoides and Trichuris trichiura ) were ubiquitous across time and space. By contrast, high numbers of food-associated cestodes ( Diphyllobothrium latum and Taenia saginata ) were restricted to medieval Lübeck. The presence of these cestodes and changes in their prevalence at approximately 1300 CE indicate substantial alterations in diet or parasite availability. Trichuris trichiura ITS-1 sequences grouped into two clades; one ubiquitous and one restricted to medieval Lübeck and Bristol. The high sequence diversity of T.t .ITS-1 detected in Lübeck is consistent with its importance as a Hanseatic trading centre. Collectively, these results introduce molecular archaeoparasitology as an artefact-independent source of historical evidence.